Autonomic neuropathies. Issue 1 (14th September 2020) - Kaur, Divpreet; Tiwana, Harmanpreet; Stino, Amro; Sandroni, Paola
Abstract: Autonomic neuropathies represent a complex group of disorders that preferentially target autonomic fibers and can be classified as either acute/subacute or chronic in onset. Acute‐onset autonomic neuropathies manifest with such conditions as paraneoplastic syndromes, Guillain‐Barre syndrome, Sjögren syndrome, infection, or toxins/chemotherapy. When the presentation is acute, immune‐mediated, and without a secondary cause, autoimmune autonomic ganglionopathy is likely, and should be considered for immunotherapy. Of the chronic‐onset forms, diabetes is the most widespread and disabling, with autonomic impairment portending increased mortality and cardiac wall remodeling risk. Acquired light chain (AL) and transthyretin (TTR) amyloidosis represent two other key etiologies, with TTR amyloidosis now amenable to newly‐approved gene‐modifying therapies. The COMPASS‐31 questionnaire is a validated outcome measure that can be used to monitor autonomic severity and track treatment response. Symptomatic treatments targeting orthostatic hypotension, among other symptoms, should be individualized and complement disease‐modifying therapy, when possible.